(untitled) (International Journal of Engineering and Computer Science, 2015)
Image Fusion is a process of combining image details from a number of images into a single image, where the resultant fused image will have most of the details and is more informative and complete than any of the input images. Image fusion techniques can increase the quality and populate the application domain of these data. In this paper we present a detailed study and survey on some of the image fusion techniques for image fusion like, primitive fusion (Averaging Method, Select Maximum, and Select Minimum), Discrete Wavelet transform based fusion, Principal component analysis (PCA) based fusion etc. Study and Comparison of all the techniques helps to determine the better approach for its future research and implementation.